Hardware-software extensions to a softcore processor for FPGA-based adaptive PID control - Gomes, Tiago Manuel Ribeiro (2013)
Embedded Systems were traditionally implemented as a microprocessor surrounded by on-board peripherals, specifically assembled for a given application. Several Commercial Off-The Shelf solutions already provide a variety of on-chip custom modules, which allow a higher performance, smaller power consumption solution for a variety of applications. The advent of Field Programmable Gate Arrays (FPGA) allowed custom chips to be designed on a per-application basis, with fine-grain control over hardware/software partitioning. This paper presents a case study about the integration of an adaptive control system on a softcore processor. An MRAC-PID custom hardware module was developed and implemented on FPGA, taking advantage of the extensibility capabilities of the utilized softcore. Results demonstrate how software to hardware migration can accelerate system performance and maximize application parallelism.